Molecular Profiles of Parvalbumin-Immunoreactive Neurons in the Superior Temporal Cortex in Schizophrenia - Pietersen, Charmaine Y.; Mauney, Sarah A.; Kim, Susie S.; Passeri, Eleonora; Lim, Maribel P.; Rooney, Robert J.; Goldstein, Jill M.; Petreyshen, Tracey L.; Seidman, Larry J.; Shenton, Martha E.; Mccarley, Robert W.; Sonntag, Kai-C.; et al. (Journal of neurogenetics, 2014)
Abstract Dysregulation of pyramidal cell network function by the soma- and axon-targeting inhibitory neurons that contain the calcium-binding protein parvalbumin (PV) represents a core pathophysiological feature of schizophrenia. In order to gain insight into the molecular basis of their functional impairment, we used laser capture microdissection (LCM) to isolate PV-immunolabeled neurons from layer 3 of Brodmann's area 42 of the superior temporal gyrus (STG) from postmortem schizophrenia and normal control brains. We then extracted ribonucleic acid (RNA) from these neurons and determined their messenger RNA (mRNA) expression profile using the Affymetrix platform of microarray technology. Seven hundred thirty-nine mRNA transcripts were found to be differentially expressed in PV neurons in subjects with schizophrenia, including genes associated with WNT (wingless-type), NOTCH, and PGE2 (prostaglandin E2) signaling, in addition to genes that regulate cell cycle and apoptosis. Of these 739 genes, only 89 (12%) were also differentially expressed in pyramidal neurons, as described in the accompanying paper, suggesting that the molecular pathophysiology of schizophrenia appears to be predominantly neuronal type specific. In addition, we identified 15 microRNAs (miRNAs) that were differentially expressed in schizophrenia; enrichment analysis of the predicted targets of these miRNAs included the signaling pathways found by microarray to be dysregulated in schizophrenia. Taken together, findings of this study provide a neurobiological framework within which hypotheses of the molecular mechanisms that underlie the dysfunction of PV neurons in schizophrenia can be generated and experimentally explored and, as such, may ultimately inform the conceptualization of rational targeted molecular intervention for this debilitating disorder.